330 Young driver crash types and lifetime care costs by posted speed limit. (1st September 2016) - Buckis, Samantha; Lenné, Mike G; Stephens, Amanda; Bingham, C Raymond; Fitzharris, Michael
Abstract : Background: Speeding is a key issue for all drivers as it influences both crash risk and crash severity. Young drivers, particularly males, are more likely to engage in speeding behaviour and speeding is a common contributing factor in young driver crashes. Greater understanding of the impact of speed and speeding on young driver crash risk and crash outcomes is required to inform the development, prioritisation and implementation of evidence-based safety interventions. Methods: In Victoria, Australia, the Transport Accident Commission (TAC) operates as the sole, statutory compensation (3 rd party insurance) scheme. The TAC has legislated responsibility for road safety and the care of persons injured in road crashes, irrespective of fault. TAC claims data for the period 2005–2013 was used to analyse the differences in crash types and injury outcomes, including cost, by posted speed limit (30, 40, 50, 60, 70, 75, 80, 90, 100 and 110 km/h). The mean and overall lifetime care costs were analysed by speed limit. Speed limit was also analysed by age, gender, location, time of day and crash type. Young drivers were split into two groups for comparison 18–21 and 22–25. Results: Over the 9-year period, 16, 794 claims were lodged to the TAC for killed or injured drivers 18–25 years of age (young drivers). The total lifetime care cost for all young drivers killed or injured in a crash was estimated to be AUD634 million. The total lifetime care cost for young male drivers was estimated to be AUD470 million compared to AUD163 million for young female drivers. 18 to 21 year old drivers accounted for AUD356 million compared to AUD279 million for 22 to 25 year old drivers. When the posted speed limit is considered, the total cost of killed or injured young drivers who crashed in 60 km/h zones (N = 3914) was estimated to be AUD70 million ( M = AUD 17, 807), compared to AUD208 million ( M = AUD 65, 580) in 100 km/h zones (N = 3173). Conclusions: Road trauma not only has an enormous impact on the lives of those involved, their families and friends, it also has a significant economic burden on our communities. This research demonstrates that speed and male gender play key roles in crash outcomes, particularly lifetime care costs, and should be essential considerations for safety interventions.